2001
DOI: 10.1163/156854001300228825
|View full text |Cite
|
Sign up to set email alerts
|

Egyptian Interstitial Copepoda Harpacticoida With the Description of Two New Species and One New Subspecies

Abstract: Nine species of Copepoda Harpacticoida were found in sandy beaches in Egypt during the period November 1994 to December 1996. Two species of the family Ectinosomatidae are new to science, Arenosetella bassantae n. sp. and Noodtiella toukae n. sp. The genus Noodtiella is new to the fauna of the Mediterranean Sea. One subspecies of the family Paramesochridae is new to science, Kliopsyllus constrictus egyptus n. subsp. The other species found are already known from the Mediterranean: Arenopontia nesaie (Cylindrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 5 publications
0
14
0
1
Order By: Relevance
“…23.9.1.1) and Alteutha has been used as a valid name in at least 25 works, published by at least 10 authors in the last 50 years (ICZN Art. 23.9.1.2) [e.g.Por 1960a;Wiborg 1964;Pallares 1968a;Fives 1969;Apostolov 1973;Gharagozlou-Van Ginneken 1976;Wells 1976Hicks 1977Hicks , 1982Hicks , 1986aCoffin 1981;McClelland 1982;Apostolov & Marinov 1988;Dahms 1992Dahms , 1993aSong & Chang 1995;Mitwally & Montagna 2001;Apostolov & Pandourski 2002;Duggan et al 2006;Kane 2007;Michels 2007;Veit-Köhler & Fuentes 2007a, 2007b. In accordance with ICZN Art.…”
Section: Junior Subjective Synonymsmentioning
confidence: 99%
See 1 more Smart Citation
“…23.9.1.1) and Alteutha has been used as a valid name in at least 25 works, published by at least 10 authors in the last 50 years (ICZN Art. 23.9.1.2) [e.g.Por 1960a;Wiborg 1964;Pallares 1968a;Fives 1969;Apostolov 1973;Gharagozlou-Van Ginneken 1976;Wells 1976Hicks 1977Hicks , 1982Hicks , 1986aCoffin 1981;McClelland 1982;Apostolov & Marinov 1988;Dahms 1992Dahms , 1993aSong & Chang 1995;Mitwally & Montagna 2001;Apostolov & Pandourski 2002;Duggan et al 2006;Kane 2007;Michels 2007;Veit-Köhler & Fuentes 2007a, 2007b. In accordance with ICZN Art.…”
Section: Junior Subjective Synonymsmentioning
confidence: 99%
“…23.9.1.2 are met (Peltidiidae is cited in e.g. Geddes 1968b;Wells 1970Wells , 1976Hicks 1977Hicks , 1982Hicks , 1986aHumes 1981bHumes , 1984Apostolov & Marinov 1988;Dahms 1992Dahms , 1993aMitwally & Montagna 2001;Seifried 2003Seifried , 2004Varela 2005;Suárez-Morales et al 2006;Veit-Köhler & Fuentes 2007a-b;Gheerardyn et al 2008;Ivanenko et al 2008), the junior synonym Peltidiidae is considered the valid name (nomen protectum) which has precedence over the older name Steropinae (nomen oblitum). Family Tisbidae Stebbing, 1910Philippi (1843 proposed the genus Idya Philippi, 1843 (type species by monotypy: Idya barbigera Philippi, 1843) while Lilljeborg (1853: 191) created the generic name Tisbe for Cyclops furcatus Baird, 1837 (type species by monotypy).…”
Section: Junior Subjective Synonymsmentioning
confidence: 99%
“…A similar raised pair of multidentate lamellae on the anal somite was described for two closely related species in the genus Noodtiella: N. ornamentalis Rao, 1987 andN. toukae Mitwally &Montagna, 2001. Based on this character and the apparent differences with Arenosetella, Wells and Rao (1987) suggested that N. ornamentalis may be placed in a genus separate from Noodtiella but refrained from formally naming and diagnosing it.…”
Section: P1mentioning
confidence: 81%
“…d Mitwally and Montagna (2001) list the formula for P2-P4 enp-2 as 221 but do not take into account the posterior surface seta; the formula is here amended to 321 e Wells and Rao's (1987) illustration of the P2 is likely to be incorrect; the distal endopod segment appears to be reversed although the spinule row marking the original subdivision is illustrated on the correct (outer) margin; given the close relationship to N. pectinata it is also conceivable that the authors overlooked the posterior surface seta on P2-P4 enp-2.…”
Section: P1mentioning
confidence: 99%
“…The 3rd segment with two terminal setae." (Mitwally and Montagna 2001). As this situation does not fit with the general pattern found in the Ectinosomatidae (Seifreid 2003), the holotype was re-examined.…”
Section: Discussionmentioning
confidence: 99%